2022
DOI: 10.1016/j.jsxm.2022.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Ejaculatory Function Following Stereotactic Body Radiation Therapy for Prostate Cancer

Abstract: Background Ejaculatory dysfunction is an important male quality of life issue which has not yet been studied in the setting of prostate stereotactic body radiation therapy (SBRT). Aim The purpose of this study is to evaluate ejaculatory function following SBRT for prostate cancer. Methods Two hundred and thirty-one patients on a prospective quality of life st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Radiation therapy is a guideline supported treatment for localized prostate cancer, and has been widely employed in contemporary practice (2). Yet, numerous studies have observed harmful side effects, including sexual dysfunction (2)(3)(4)(5)(6)(7)(8). Sexual dysfunction involves various domains including both ejaculatory (EjD) and erectile dysfunction (EF) (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation therapy is a guideline supported treatment for localized prostate cancer, and has been widely employed in contemporary practice (2). Yet, numerous studies have observed harmful side effects, including sexual dysfunction (2)(3)(4)(5)(6)(7)(8). Sexual dysfunction involves various domains including both ejaculatory (EjD) and erectile dysfunction (EF) (9).…”
Section: Introductionmentioning
confidence: 99%
“…Five studies examined impact of radiation on ejaculatory function using patient report outcome measures. The assessment methods included the Brief Sexual Function Inventory (BSFI) in two studies, the Ejaculatory Di culty Score (EJS) in one, the Orgasm Domain Score of the International Index of Erectile Function (IIEF) in another, and the Ejaculation Scale (ES-8) from the Male Sexual Health Questionnaire (MSHQ) in the nal study(4,20,21). Studies revealed a common pattern of initial decline in function scores followed by varying degrees of recovery or further deterioration over time.…”
mentioning
confidence: 99%